2019
DOI: 10.1103/physrevc.99.055808
|View full text |Cite
|
Sign up to set email alerts
|

Topology change and nuclear symmetry energy in compact-star matter

Abstract: We show that the cusp-like structure in the nuclear symmetry energy, a consequence of topology change, visible in the skyrmion lattice description of dense matter is extremely robust. It is present in the Skyrme model -with the pion field only -and is left unscathed by massive degrees of freedom such as the vector mesons ρ and ω and also the scalar meson introduced as a dilaton. It leads to the emergence of parity-doubling at the skyrmion-half-skyrmion transition and impacts on the nuclear symmetry energy "wil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…This is because Σ = qq → 0 as n → n 1/2 . It has been shown [81] that the same cusp structure is obtained with the heavy vector degrees of freedom included in HLS Lagrangian. Just the location of the cusp changes with additional degrees of freedom, with the location tending to go to higher densities the more heavy degrees of freedom are included.…”
Section: Cusp In the Nuclear Symmetry Energymentioning
confidence: 56%
“…This is because Σ = qq → 0 as n → n 1/2 . It has been shown [81] that the same cusp structure is obtained with the heavy vector degrees of freedom included in HLS Lagrangian. Just the location of the cusp changes with additional degrees of freedom, with the location tending to go to higher densities the more heavy degrees of freedom are included.…”
Section: Cusp In the Nuclear Symmetry Energymentioning
confidence: 56%
“…A surprising result found in [27] is that since Σ goes to zero as density approaches n 1/2 , there appears a cusp at n 1/2 , with the symmetry energy dropping going toward n 1/2 , then turning over and increasing as the density increases beyond n 1/2 . This cusp is highly robust against strong interactions [28] but, being semiclassical, is expected to be smoothed by higher order nuclear correlations. Also the pion mass will intervene in eliminating discontinuity in the cusp structure.…”
Section: Nuclear Symmetry Energymentioning
confidence: 98%
“…Based on what we discussed above and will develop below, it is found that the topology change is significant for developing the pseudo-conformal model (PCM) of dense nuclear matter, especially for the existence of the conformal sound velocity in compact star matter. Because of this topology change, there is a cusp structure in the symmetry energy E sym [11,89] which provides a simple mechanism for the putative soft-to-hard change in the EoS for compact stars at n ∼ 2n 0 needed to account for the observed massive ∼ 2M . In the models that resort to hadron-quark continuity in terms of specific quark degrees of freedom that are strongly coupled, the hardening of the EoS at n ∼ > 2n 0 is associated with "deconfinement" of quarks [4,23].…”
Section: Cheshire Cat Principle and Quark-hadron Continuitymentioning
confidence: 99%